1987
DOI: 10.1002/j.1537-2197.1987.tb12143.x
|View full text |Cite
|
Sign up to set email alerts
|

Tropical American Tertiary Floras and Paleoenvironments: Mexico, Costa Rica, and Panama

Abstract: Three Tertiary microfossil floras from northern Latin America are considered with reference to paleoenvironments and paleoenvironmental trends, especially paleotemperatures: Gatuncillo (middle (?) to late Eocene, Panama), Uscari (early Miocene, Costa Rica), and Paraje Solo (late Miocene, Veracruz, Mexico). The composition of the floras reflect lower temperatures in the late Miocene for terrestrial environments at ca. 18°N latitude, and temperatures comparable to the present for the middle (?) to late Eocene an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
7
0

Year Published

1990
1990
2010
2010

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 34 publications
(10 citation statements)
references
References 45 publications
3
7
0
Order By: Relevance
“…The first assumption is that vicariance events cannot explain the current distribution of the taxon under investigation. The estimated date of divergence of rattlesnakes from their common ancestor with Agkistrodon is recent enough (20-30 mya; Knight et al, 1993) to preclude vicariance via mountain forming in Central America (40-60 mya; Graham, 1989). Our application of Bremer's method meets this assumption.…”
Section: Discussionsupporting
confidence: 50%
See 2 more Smart Citations
“…The first assumption is that vicariance events cannot explain the current distribution of the taxon under investigation. The estimated date of divergence of rattlesnakes from their common ancestor with Agkistrodon is recent enough (20-30 mya; Knight et al, 1993) to preclude vicariance via mountain forming in Central America (40-60 mya; Graham, 1989). Our application of Bremer's method meets this assumption.…”
Section: Discussionsupporting
confidence: 50%
“…Thus, increased confidence in inferring the ancestral habitat type could emerge only if it can be shown that habitats in the ancestral area have changed little since the initial divergence. Palynological data indicate that pollen typical of the present pine-oak habitats of the region were already present in the middle to late Tertiary (Graham, 1987(Graham, , 1989. Armstrong and Murphy (1979) give vegetational associations of extant rattlesnakes in Mexico.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Raven (1963) suggested that such plants could have migrated at the end of the Pliocene or in Pleistocene, during some of the last cold periods that expanded the polar regions in both hemispheres. Graham (1987) and Ball (1990) agree with Raven (1963) in chronological estimations of migrations, but differ in the proposed mechanism of dispersal. Raven (1963) proposed a direct jump between the adjacent regions of both hemispheres, whereas Graham (1987) and Ball (1990), following Guppy's (1917) hypothesis, suggested a migration pathway through mountain chains (mountain hopping) across tropical regions where climatic conditions were very similar to the polar zones.…”
Section: Parallel Evolution and Long-distance Dispersalmentioning
confidence: 62%
“…Graham (1987) and Ball (1990) agree with Raven (1963) in chronological estimations of migrations, but differ in the proposed mechanism of dispersal. Raven (1963) proposed a direct jump between the adjacent regions of both hemispheres, whereas Graham (1987) and Ball (1990), following Guppy's (1917) hypothesis, suggested a migration pathway through mountain chains (mountain hopping) across tropical regions where climatic conditions were very similar to the polar zones. The same hypothesis has recently been documented on the basis of AFLP results in Carex canescens, C. echinata, C. lachenalii, and C. magellanica (Vollan et al, 2006).…”
Section: Parallel Evolution and Long-distance Dispersalmentioning
confidence: 62%